Florida Dairy Farm Situation and Outlook 2006 - Russ Giesy; Albert De Vries; Dave Bray; Dan Webb (EDIS)
This document is AN160, one of a series of the Department of Animal Sciences, UF/IFAS Extension. Original publication date: January 2006.